An atlas of microtubule lattice parameters regulated through ligand binding to the microtubule-stabilizing sites - Daniel Lucena-Agell; Óscar Fernández; Rebeca París-Ogáyar; Juan Estévez-Gallego; Denisa Ondrúšková; Beatriz Álvarez-Bernad; Francesca Bonato; Jaime Larraga; Diego Ortíz de Elguea; Gregorio Javier Cano; Maarten Scheers; Hiroshi Imai; et al. (Proceedings of the National Academy of Sciences, 2026)
Microtubules are dynamic cytoskeletal polymers whose lattice architecture regulates force generation, nucleotide hydrolysis, and recognition by motor proteins and microtubule-associated proteins (MAPs). Microtubule-stabilizing agents (MSAs), including taxanes and laulimalide/peloruside-site ligands, suppress depolymerization by binding to defined lattice sites, yet stabilization is not structurally neutral. How ligand chemistry reshapes lattice organization and function remains unresolved. Here, we address three mechanistic questions. First, do distinct ligand classes induce defined lattice states? Using X-ray fiber diffraction, we show that MSAs selectively stabilize two preferred longitudinal conformations, a compact state (~4.06 nm monomer rise) and an expanded state (~4.17 nm), while modulating lateral organization reflected in shifts in mean MT radius. These axial spacings cluster around discrete values across chemotypes, indicating stabilization of preexisting conformational minima rather than continuous distortion. Second, are these states interconvertible upon changes in ligand occupancy? Time-resolved diffraction reveals that longitudinal transitions occur within seconds of ligand addition even at substoichiometric occupancy, whereas, lateral equilibration proceeds slower, consistent with redistribution within heterogeneous protofilament organizations. Third, do such structural states alter nucleotide hydrolysis and motor/MAP behavior? Expanded lattices are associated with reduced apparent GTP hydrolysis rates under steady-state assembly conditions and altered kinesin motility, whereas compact lattices preferentially promote tau binding and distinct motor interaction profiles. Together, these findings establish longitudinal lattice conformation as a regulatory parameter and position MSAs as chemical tools that bias a dynamic structural landscape with predictable catalytic and transport consequences.